Deletion of miPEP in adipocytes protects against obesity and insulin resistance by boosting muscle metabolism - Alexis Diaz-Vegas; Kristen C. Cooke; Harry B. Cutler; Belinda Yau; Stewart W.C. Masson; Dylan Harney; Oliver K. Fuller; Meg Potter; Søren Madsen; Niamh R. Craw; Yiju Zhang; Cesar L. Moreno; et al. (Elsevier, 2024)
Mitochondria facilitate thousands of biochemical reactions, covering a broad spectrum of anabolic and catabolic processes. Here we demonstrate that the adipocyte mitochondrial proteome is markedly altered across multiple models of insulin resistance and reveal a consistent decrease in the level of the mitochondrial processing peptidase miPEP. Objective: To determine the role of miPEP in insulin resistance. Methods: To experimentally test this observation, we generated adipocyte-specific miPEP knockout mice to interrogate its role in the aetiology of insulin resistance. Results: We observed a strong phenotype characterised by enhanced insulin sensitivity and reduced adiposity, despite normal food intake and physical activity. Strikingly, these phenotypes vanished when mice were housed at thermoneutrality, suggesting that metabolic protection conferred by miPEP deletion hinges upon a thermoregulatory process. Tissue specific analysis of miPEP deficient mice revealed an increment in muscle metabolism, and upregulation of the protein FBP2 that is involved in ATP hydrolysis in the gluconeogenic pathway. Conclusion: These findings suggest that miPEP deletion initiates a compensatory increase in skeletal muscle metabolism acting as a protective mechanism against diet-induced obesity and insulin resistance.